THE FIGURATIVE AND SEMANTIC SERIES OF THE NOVEL "BERESTECHKO" IN THE GRAPHIC PRESENTATION BY SERGIY YAKUTOVYCH - Михайлова , Р. Д.; Гула, Є. П.; Березницька, М. О. (Art and Design, 2024)
The purpose. To explore S. Yakutovych’s idea of creating an illustration series for the novel Berestechko by Lina Kostenko and the ways of its implementation; to analyze the artist’s creative approaches in the design of the selected book; to find out the specifics of artistic decisions and their role in creating the visual content of the publication. Methodology. The study is based on historical and theoretical, empirical, comparative, biographical, art historical, and cultural methodology; functional and morphological analysis is also used. The results. The study of the creative tools of S. Yakutovych, one of the leading Ukrainian artists of the second half of the twentieth and early twenty-first centuries, revealed the peculiarities of his work on the text and the publication as a whole, as well as, on this example, the specifics of the process of formation and development of book design in Ukraine. The scientific analysis of the publication "Berestechko" showed the process of the artist’s work on the design of the book as an integral system, unified in the ratio of the figurative and content series, the organization of the book block, and the constructive and design solution. It has been found that in the process of developing this unity, the algorithm codes transform the work material into stylistically expressive images, from which the artist forms a semantic and figurative artistic series, while the formative elements are aimed at the structural organization of the book. The example of the artistic solution of the novel in verse "Berestechko" demonstrates the amplitude of possibilities for creative coverage and transformation of the source material in a particular project. It is concluded that S. Yakutovych’s visualization of a literary text of historical and philosophical orientation belongs to the best traditions of the Ukrainian graphic art school, which in the second half of the twentieth and early twenty-first centuries became the basis for updating the book design and remains a valuable artistic example of the implementation of creative ideas in book design. The scientific novelty of the study the research is aimed at studying the ways of forming the image of the book by Ukrainian artists in the second half of the twentieth and early twenty-first centuries, revealing the ideological approaches and linguistic and graphic means in S. Yakutovych’s creative practice that are relevant for contemporary book designers. On the basis of S. Yakutovych’s interviews, the article reveals the nuances of the artist’s creative approaches and artistic vision, which were reflected in his work with text. The practical significance of the research is of the study is to expand the information and deepen the practical skills of a book designer working with a literary text, mastering the mechanisms of creating and presenting graphic design samples. The results prove the promising potential of the traditions of Ukrainian graphic art in the implementation of modern design solutions. The materials of this work can be used in the educational process and practical activities of book designers.